Aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite, preparation method and application

CN122687008APending Publication Date: 2026-09-04CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610487482.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-14
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0007]本发明的目的是解决现有碳纳米管增强铝镁硅合金基复材存在的增强相易团聚、界面易生成脆性相的问题

Benefits of technology

本发明通过独创的“化学-物理协同预处理”工艺,有效解决了碳纳米管在铝基体中极易团聚的难题,实现了增强相的纳米级均匀分散。具体而言,采用浓硝酸对碳纳米管进行酸化处理,在去除无定形碳杂质的同时在管壁引入羧基等含氧官能团,这种表面改性显著改善了碳纳米管与金属基体的润湿性及界面相容性,降低了界面能;随后配合特定分散剂与高强度超声分散,从源头上克服了碳纳米管间极强的范德华力,使其在溶剂中实现单分散。在此基础上,利用高能球磨工艺将预分散的碳纳米管机械嵌入变形后的合金粉末中,构建“核-壳”结构复合粉末,这种微观结构设计不仅增加了碳纳米管与基体的接触面积,更防止了后续高温工序中碳纳米管的二次团聚,为载荷的有效传递奠定了微观结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122687008A_ABST
    Figure CN122687008A_ABST
Patent Text Reader

Abstract

The application discloses an aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite and a hot extrusion preparation method thereof, and belongs to the field of metal matrix composite manufacturing. The method aims to solve the problems of reinforcement phase agglomeration, interface reaction to generate brittle Al4C3 phase and unstable forming quality. The steps include: acidizing and ultrasonic dispersion pretreatment of multi-walled carbon nanotubes; mixing the dispersion liquid with aluminum-magnesium-silicon alloy powder and performing high-energy ball milling to form a core-shell structure composite powder; cold pressing to form a preform; hot extrusion forming under the conditions of a temperature of 400 to 500 DEG C, an extrusion ratio of 10:1 to 25:1, a speed of 1 to 10 mm / s and online quenching, followed by solid solution aging heat treatment. The application realizes uniform dispersion distribution of carbon nanotubes through chemical and physical cooperative pretreatment and mechanical ball milling, effectively inhibits the generation of interface brittle Al4C3 phase by using a low-temperature large deformation process, and significantly improves the interface bonding quality and matrix density. The prepared composite has a hardness of 150 HV or more, and excellent mechanical properties and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal matrix composite manufacturing, specifically relating to an aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite, its preparation method, and its application. Background Technology

[0002] As power grid construction extends to high-voltage, long-distance, and complex geographical environments, the performance requirements for key components of transmission lines are becoming increasingly stringent. Power fittings, as core components connecting conductors, insulators, and towers, operate for extended periods in complex outdoor environments, simultaneously bearing the combined effects of mechanical loads, electrical loads, and the natural environment. Especially in inland areas with strong winds and sandstorms, or in coastal areas with strong winds and high salt spray, traditional power fittings are mainly made of carbon steel or alloy structural steel such as Q235B and 35CrMo, with a hot-dip galvanized surface for corrosion protection. However, the high density of steel results in a high weight for the fittings, significantly increasing the load on the towers and the difficulty of construction and maintenance. Furthermore, in strong wind and sand environments, the scouring of high-speed sand particles causes rapid wear and detachment of the galvanized layer, exposing the substrate and making it susceptible to coupled corrosion and wear failure, seriously threatening the safe operation of the power grid. Therefore, developing lightweight, high-strength, tough, and wear-resistant new fitting materials has become an urgent need for the industry.

[0003] Aluminum-magnesium-silicon alloys are heat-treatable aluminum alloys with low density, high specific strength, excellent corrosion resistance, and good electrical and thermal conductivity. They are considered ideal matrix materials for achieving lightweight fittings, replacing traditional steel materials. To further improve their service life under extreme conditions, the introduction of carbon nanotubes as a reinforcing phase to prepare aluminum-based composites has become a research hotspot. Carbon nanotubes, with their extremely high axial strength, excellent elastic modulus, and unique nanoscale effects, can theoretically significantly improve the mechanical properties and wear resistance of the metal matrix.

[0004] However, existing technologies still face numerous bottlenecks in the actual preparation of carbon nanotube-reinforced aluminum-magnesium-silicon alloy composites. First, carbon nanotubes have extremely high aspect ratios and specific surface areas, resulting in strong inter-tube van der Waals forces that easily lead to agglomeration, making it difficult to achieve uniform dispersion within the metal matrix. Agglomerated carbon nanotubes not only fail to provide reinforcement but also become stress concentration sources, inducing crack initiation and reducing the material's plasticity and fatigue life. Second, severe interfacial reactions exist during the preparation of aluminum-based composites. Under high-temperature conditions, carbon nanotubes readily react chemically with the aluminum matrix to form the brittle Al4C3 phase. This interfacial product is needle-like or plate-like, brittle and hard, severely disrupting the matrix continuity and significantly reducing the interfacial bonding strength and corrosion resistance of the composite. Especially in humid or corrosive environments, the hydrolytic properties of Al4C3 accelerate material failure.

[0005] Currently, powder metallurgy combined with hot extrusion is a common process for preparing high-performance aluminum-based composites. This process achieves material densification through the triaxial compressive stress state of hot extrusion and refines grains through shear deformation. However, existing hot extrusion technologies are still immature for carbon nanotube-reinforced aluminum-magnesium-silicon alloy systems. On the one hand, effectively breaking up carbon nanotube aggregates and achieving their directional alignment along the extrusion direction during hot extrusion, while avoiding microstructure inhomogeneity caused by differences in powder flowability, is a challenge for process control. On the other hand, aluminum-magnesium-silicon alloys have specific hot working windows, and existing extrusion parameters (such as temperature, extrusion ratio, and deformation rate) often fail to coordinate the relationship between the dispersion requirements of the carbon nanotube reinforcing phase and the dynamic recrystallization behavior of the matrix. If the extrusion temperature is too high, the interfacial reaction intensifies; if the temperature is too low or the deformation is insufficient, it is difficult to eliminate porosity defects and fully utilize the synergistic effect of fine-grain strengthening and dispersion strengthening. Furthermore, the complexity of metal flow during hot extrusion may lead to defects such as coarse-grained rings and shrinkage tails, further affecting the consistency and reliability of the product.

[0006] In summary, existing preparation techniques still have significant shortcomings in terms of the easy agglomeration of reinforcing phases and the easy formation of brittle phases at the interface, which limits the promotion and application of high-performance carbon nanotube-reinforced aluminum-magnesium-silicon alloy composites in the field of power fittings. Summary of the Invention

[0007] The purpose of this invention is to solve the problems of easy agglomeration of the reinforcing phase and easy formation of brittle phases at the interface in existing carbon nanotube-reinforced aluminum-magnesium-silicon alloy composites.

[0008] The objective of this invention is achieved through the following technical solution: A method for preparing an aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite includes the following steps: Carbon nanotube pretreatment steps: Acidify the carbon nanotubes, then add a dispersant and ultrasonically disperse them to obtain a carbon nanotube suspension; Mechanical composite step: The carbon nanotube suspension is mixed with aluminum-magnesium-silicon alloy powder and then ball-milled under a protective atmosphere to obtain composite powder; Preform preparation steps: The composite powder is cold-pressed to obtain a preform; Hot extrusion molding step: The preform is heated to 400~500℃ and hot extruded under the conditions of extrusion ratio of 10:1~25:1 and extrusion speed of 1~10 mm / s to obtain the molded composite material. Heat treatment steps: The molded composite material is subjected to solution treatment and artificial aging treatment to obtain the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material.

[0009] Preferably, in the carbon nanotube pretreatment step, the acidification treatment is performed by reflux treatment with concentrated nitric acid at 60~80°C for 2~4 hours; the dispersant is a nonionic surfactant or anionic dispersant, and the mass ratio of the dispersant to the carbon nanotubes is 6:1~10:1.

[0010] Preferably, in the mechanical compounding step, the ball-to-material ratio of the high-energy ball mill is 5:1 to 15:1, the rotation speed is 200 to 400 rpm, the ball milling time is 2 to 8 hours, and an intermittent ball milling mode is adopted.

[0011] Preferably, in the preform preparation step, the temperature of the hot extrusion molding is 450~480℃.

[0012] Preferably, in the hot extrusion molding step, after the hot extrusion molding is completed, the extruded material is immediately subjected to online water mist quenching or forced air cooling.

[0013] Preferably, in the heat treatment step, the solution treatment temperature is 520~560℃, and the solution is held for 0.5~2 hours before water quenching; the artificial aging temperature is 160~180℃, and the aging time is 6~12 hours.

[0014] More specifically, the preparation method includes the following steps: 1. Pretreatment and dispersion of carbon nanotubes Raw material selection: Multi-walled carbon nanotubes (MWCNTs) with a purity >95%, outer diameter 10~30 nm, and length 1~10 μm are selected. The matrix alloy is an Al-Mg-Si alloy powder (e.g., corresponding to AA6061 or AA6082 composition) prepared by gas atomization or rotating electrode method, with a particle size distribution of 15~75 μm and an oxygen content of less than 0.15 wt%.

[0015] Surface cleaning: Place CNTs in concentrated nitric acid (or mixed acid) and reflux at 60~80℃ for 2~4 hours to remove impurities such as amorphous carbon and introduce carboxyl (-COOH) functional groups to improve their wettability with metals.

[0016] Dispersion preparation: Acid-treated CNTs were washed with deionized water until neutral and dried. Then, they were added to anhydrous ethanol or isopropanol at a mass ratio of 6:1 to 10:1 with a dispersant (such as nonionic surfactant TNADIS, polyvinylpyrrolidone PVP, or anionic dispersant). The CNTs were then ultrasonically dispersed using an ultrasonic cell disruptor at 300-500 W for 30-60 minutes under ice-water bath conditions to obtain a homogeneous and stable CNT suspension.

[0017] 2. Mechanical compounding for preparing composite powders Mixing: The above CNT suspension is slowly added dropwise to the aluminum-magnesium-silicon alloy powder at the target mass fraction (0.2~3.0 wt%), while stirring at low speed in a planetary mixer to ensure that the liquid uniformly wets the powder surface.

[0018] High-energy ball milling: The mixed wet powder is transferred to the grinding jar of a high-energy ball mill (such as a planetary ball mill or a stirred mill). Stainless steel or carbide grinding balls are used, with a ball-to-powder ratio controlled between 5:1 and 15:1. To prevent excessive cold welding and oxidation, the ball milling process is carried out under argon protection. The ball milling speed is 200-400 rpm, and the total time is 2-8 hours. Intermittent ball milling (e.g., running for 15 minutes, then pausing for 5 minutes) is used to prevent overheating. This process aims to mechanically embed or firmly attach CNTs to the surface and interior of the deformed alloy powder, forming a "core-shell" structured composite powder.

[0019] Drying and sieving: The ball-milled composite powder was dried in a vacuum drying oven at 60-80°C for 12 hours. It was then sieved through a 200-mesh sieve to remove any small amounts of hard agglomerates that might have formed.

[0020] 3. Cold pressing to prepare preforms Molding and Pressing: The composite powder is loaded into a cylindrical steel mold. It is then cold-pressed on a single-axis hydraulic press at a pressure of 300-600 MPa for 1-3 minutes to form a preform with a relative density of 80-85%. To facilitate demolding, the inner wall of the mold can be sprayed with zinc stearate as a lubricant.

[0021] Pre-treatment of billet: The pressed billet is heated to 400-450°C at a rate of 5-10°C / min in a vacuum or flowing argon environment and held for 1-2 hours to perform pre-sintering to remove residual dispersant and some gas, and to initially improve the strength of the billet, which is conducive to subsequent hot extrusion operations.

[0022] 4. Hot extrusion molding Equipment and molds: A horizontal hydraulic extrusion press is used. The mold system includes an extrusion cylinder, extrusion gaskets, and a flat or streamlined mold with a cone angle of 60°~90°. The molds and extrusion cylinder are preheated to 300~350°C before use.

[0023] Ingot heating: Place the pre-made ingot in a box furnace with a protective atmosphere (high-purity argon or nitrogen) and heat it to 400~500℃, preferably 450~480℃, and hold it for 1~3 hours to make the overall temperature of the ingot uniform and ensure that the temperature is lower than the starting temperature (about 500℃ or above) at which aluminum and carbon react significantly.

[0024] Extrusion process: Extrusion ratio: set to 10:1 to 25:1. A higher extrusion ratio provides greater shear deformation, effectively breaking up CNT agglomerates, promoting their directional alignment along the extrusion direction, and achieving complete densification of the matrix.

[0025] Extrusion speed: Controlled within the range of 1~10 mm / s. A lower extrusion speed is conducive to uniform heat distribution and reduces excessive local temperature rise caused by deformation heat.

[0026] Lubrication: Use glass lubricant or graphite-based lubricant between the billet and the extrusion cylinder and die to reduce friction and die wear.

[0027] Demolding and Cooling: After the extruded bars or profiles are demolded, they can be quenched by online water mist or forced air cooling to quickly pass through the solution temperature range, retaining Mg and Si atoms in the aluminum matrix and creating conditions for subsequent aging strengthening.

[0028] 5. Subsequent heat treatment (T6 state) Solution treatment: Hold the extruded material in a salt bath furnace or air circulation furnace at 520~560℃ (adjusted according to the specific alloy composition) for 0.5~2 hours, and then quickly quench it in water.

[0029] Artificial aging: Aging is carried out in an oil bath or oven at 160~180℃ for 6~12 hours to obtain peak strength (T6 condition). Based on the same inventive concept, the present invention also provides an aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material, characterized in that it is prepared by the method described above, the composite material includes an aluminum-magnesium-silicon alloy matrix and carbon nanotubes dispersed in the matrix, the carbon nanotubes are oriented or strip-shaped distributed along the extrusion direction, and there is no large amount of Al4C3 brittle phase at the interface between the carbon nanotubes and the aluminum matrix.

[0030] Preferably, the mass fraction of the carbon nanotubes in the composite material is 0.2 wt% to 3.0 wt%.

[0031] Preferably, the Vickers hardness of the composite material is above 150 HV.

[0032] Based on the same inventive concept, this invention also provides the application of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite as described above in the preparation of power fittings, or in aerospace structural components, or in new energy vehicle battery trays, or in lightweight automotive body frames.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention effectively solves the problem of easy agglomeration of carbon nanotubes in an aluminum matrix through a unique "chemical-physical synergistic pretreatment" process, achieving nanoscale uniform dispersion of the reinforcing phase. Specifically, concentrated nitric acid is used to acidify the carbon nanotubes, removing amorphous carbon impurities while introducing oxygen-containing functional groups such as carboxyl groups into the tube walls. This surface modification significantly improves the wettability and interfacial compatibility between carbon nanotubes and the metal matrix, and reduces the interfacial energy. Subsequently, a specific dispersant and high-intensity ultrasonic dispersion are used to overcome the extremely strong van der Waals forces between carbon nanotubes at the source, enabling them to achieve monodispersity in the solvent. Based on this, a high-energy ball milling process is used to mechanically embed the pre-dispersed carbon nanotubes into the deformed alloy powder, constructing a "core-shell" structured composite powder. This microstructure design not only increases the contact area between the carbon nanotubes and the matrix but also prevents secondary agglomeration of carbon nanotubes during subsequent high-temperature processes, laying a microstructural foundation for effective load transfer.

[0034] In the hot extrusion molding stage, this invention creatively sets a low-temperature extrusion window of 400~500℃ and a high extrusion ratio parameter system of 10:1 to 25:1, achieving synergistic control of interfacial reaction and microstructure densification. This temperature range is strictly controlled below the critical temperature for the formation of brittle Al4C3 phase in the aluminum-carbon reaction, thermodynamically inhibiting the occurrence of harmful interfacial reactions, avoiding the weakening of interfacial bonding strength and stress concentration of brittle phases, thus ensuring the strength and toughness matching of the composite material. The intense shear deformation caused by the high extrusion ratio generates huge frictional heat and plastic rheology between powder particles, further breaking down any possible residual micro-agglomerates, promoting the directional alignment of carbon nanotubes along the extrusion direction, and simultaneously achieving matrix grain refinement and complete material densification, eliminating pore defects, and fully leveraging the dual effects of fine grain strengthening and dispersion strengthening.

[0035] Furthermore, this invention introduces an online quenching process immediately after extrusion, cleverly utilizing the residual heat from extrusion deformation to achieve rapid solid solution of alloying elements. By rapidly cooling and bypassing the solid solubility curve, Mg and Si atoms are supersaturated and dissolved in the aluminum matrix, effectively avoiding coarsening of precipitated phases caused by high-temperature holding. This creates ideal thermodynamic conditions for the dispersed precipitation of nanoscale strengthening phases during subsequent artificial aging, significantly improving the yield strength and hardness of the material. In summary, this invention, through the organic synergy and precise parameter matching of various process steps, constructs a complete technical logic closed loop from nanoscale dispersion control to macroscopic forming and densification. The final composite material produced achieves a hardness of over 150 HV, with significantly improved mechanical properties, wear resistance, and electrical conductivity. Moreover, the process is highly efficient and stable, possessing significant industrial application value. Attached Figure Description

[0036] Figure 1 This is a metallographic image of a longitudinal section of Embodiment 1 of the present invention.

[0037] Figure 2 This is a bright-field image of the compressed state in Example 1.

[0038] Figure 3 This is the peak-aged transmission bright-field image of Example 1.

[0039] Where: μm is the unit of length micrometer (micron); nm is the unit of length nanometer (nanometer). Detailed Implementation

[0040] The technical solution will be further described below with reference to the accompanying drawings and specific embodiments to help understand the content of the present invention.

[0041] Example 1 (Base Example) A method for preparing an aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite includes the following steps: Carbon nanotube pretreatment steps: Acidify the carbon nanotubes, then add a dispersant and ultrasonically disperse them to obtain a carbon nanotube suspension; Mechanical composite step: The carbon nanotube suspension is mixed with aluminum-magnesium-silicon alloy powder and then ball-milled under a protective atmosphere to obtain composite powder; Preform preparation steps: The composite powder is cold-pressed to obtain a preform; Hot extrusion molding step: The preform is heated to 400~500℃ and hot extruded under the conditions of extrusion ratio of 10:1~25:1 and extrusion speed of 1~10 mm / s to obtain the molded composite material. Heat treatment steps: The molded composite material is subjected to solution treatment and artificial aging treatment to obtain the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material.

[0042] The objective of this embodiment is to prepare a composite material with a CNT content of 1.0 wt%, demonstrating the typical effect of the complete process chain of the present invention.

[0043] The aluminum-magnesium-silicon alloy powder used is: gas-atomized 6061 aluminum alloy powder (composition: Mg 1.0%, Si 0.6%, Cu 0.28%, balance Al), with a particle size distribution of 45~106 μm.

[0044] The carbon nanotubes used are multi-walled carbon nanotubes (MWCNTs) with a purity >98%, an outer diameter of 20~30 nm, and a length of 10~20 μm.

[0045] 1. The CNT (carbon nanotube) pretreatment process is as follows: CNTs were placed in 65% concentrated nitric acid and refluxed at 70°C for 3 hours, then washed with deionized water until pH neutral, and vacuum dried at 80°C for 12 hours.

[0046] Take 1.5 g of the treated CNT and 0.2 g of the nonionic dispersant TNADIS and add them together to 200 ml of anhydrous ethanol.

[0047] Disperse the cells in an ice-water bath for 45 minutes using an ultrasonic cell disruptor (450W) to obtain a uniform black suspension.

[0048] 2. The composite powder preparation process (mechanical composite steps) is as follows: The above suspension was slowly added dropwise to 148.5 grams of aluminum powder while being stirred at low speed in a mixer.

[0049] Transfer the mixture into a planetary ball mill jar and add stainless steel grinding balls (ball-to-material ratio 10:1). After evacuation, purge with high-purity argon for protection.

[0050] Ball mill at 350 rpm for 4 hours (run for 30 minutes, then pause for 10 minutes to cool down).

[0051] After ball milling, the powder was vacuum dried at 80°C for 12 hours and then passed through a 200-mesh sieve.

[0052] 3. Preform preparation: The composite powder was cold-pressed at 500 MPa into a preform of Φ40 mm × 50 mm with a relative density of approximately 82%.

[0053] 4. Hot extrusion: The billet is preheated at 450°C for 2 hours in flowing argon gas.

[0054] On a horizontal extrusion press, the billet and die are heated to 470°C. Using a glass lubricating pad, it is extruded into a Φ10 mm round bar at an extrusion ratio of 20:1 and an extrusion speed of 2 mm / s. Immediately after demolding, it is water-spray quenched.

[0055] 5. Heat treatment: The extruded bar is subjected to T6 treatment: solution treatment at 535℃ for 1 hour (water quenching), followed by artificial aging at 175℃ for 8 hours to obtain the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite.

[0056] The mechanical properties of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite prepared in this embodiment were tested. The test data are as follows: yield strength (YS) 385 MPa, tensile strength (UTS) 420 MPa, elongation (EL) 8.5%, and Vickers hardness 151 HV.

[0057] The conductivity of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite prepared in this embodiment was tested, and the conductivity was 52% IACS (International Standard for Annealed Copper).

[0058] Figure 1This is a metallographic image of the longitudinal section of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material in this embodiment.

[0059] Figure 2 This is a bright-field image of the extruded state of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material in this embodiment.

[0060] Figure 3 This is the peak-time transmission bright-field image of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite in this embodiment.

[0061] The purpose of this invention is to address key issues encountered in the hot extrusion preparation of carbon nanotube-reinforced aluminum-magnesium-silicon alloy matrix composites, such as reinforcing phase agglomeration, formation of brittle interfacial phases, poor matching of process parameters, and unstable molding quality. It provides a method for preparing aluminum-based composite materials that combines process feasibility and performance reliability. By optimizing the pretreatment process of carbon nanotubes, controlling the temperature-pressure-speed parameter system of hot extrusion, and introducing an interfacial regulator to suppress the formation of the brittle Al4C3 phase, uniform dispersion of carbon nanotubes in the aluminum-magnesium-silicon alloy matrix is ​​achieved, improving the interfacial bonding between the matrix and the reinforcing phase. Simultaneously, the dynamic recrystallization behavior during hot extrusion and the precipitation law of age-strengthening phases in the matrix are coordinated to avoid molding defects such as coarse grain rings and tailing. Ultimately, a carbon nanotube-reinforced aluminum-magnesium-silicon alloy matrix composite material with excellent mechanical properties, wear resistance, and stability is prepared. This material can meet the application requirements of power fittings in high-wind areas for lightweight, high wear resistance, and corrosion resistance, breaking through the performance bottlenecks of traditional steel fittings and ordinary aluminum-based materials, and providing technical support for the material upgrade of key components in power transmission lines.

[0062] Example 2 (Low CNT content, lateral remodeling / conductivity) Objective: To demonstrate the superior comprehensive properties of composite materials with low CNT content.

[0063] Parameter change: CNT content changed to 0.5 wt%. CNT pretreatment is the same as in Example 1.

[0064] Composite powder preparation: ball milling time was shortened to 3 hours (other aspects are the same as in Example 1).

[0065] Hot extrusion: The process parameters are exactly the same as in Example 1 (470°C, extrusion ratio 20:1).

[0066] Test results: 1. Mechanical properties: Yield strength YS 355 MPa, tensile strength UTS 390 MPa, elongation EL 12.0%.

[0067] 2. Conductivity: 58% IACS.

[0068] Analysis: Due to the low CNT content and good dispersion, the damage to the plasticity and conductivity of the matrix is ​​less, resulting in better ductility and conductivity, while the strength is still significantly higher than that of the unreinforced matrix alloy (T6 state 6061 alloy typical UTS is about 310 MPa).

[0069] The aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite obtained by this invention has uniform dispersion: the combination of "liquid phase pretreatment + high-energy ball milling" solves the agglomeration problem of carbon nanotubes from the source, laying the foundation for uniform dispersion in subsequent hot extrusion.

[0070] 2. Interface Optimization: The hot extrusion temperature window (400~500℃) controlled by this invention is lower than the temperature at which aluminum and carbon react significantly, and combined with the rapid extrusion process, it effectively suppresses the formation of the brittle Al4C3 phase. The large strain generated by extrusion helps to achieve mechanical interlocking and physical bonding between carbon nanotubes and the aluminum matrix.

[0071] The carbon nanotube-reinforced composite material with an aluminum-magnesium-silicon alloy matrix of the present invention exhibits significantly improved performance: the carbon nanotubes in the prepared composite material are well dispersed and firmly bonded to the matrix, serving as an effective load-transfer reinforcement. Compared with unreinforced aluminum-magnesium-silicon alloys, its hardness can be increased by 30% to 50% or more.

[0072] The process of this invention is highly efficient: the method combines powder metallurgy with hot extrusion forming, the process is relatively simple, and it is suitable for large-scale production.

[0073] Example 3 (High CNT content, focusing on strength) Objective: To verify the ability of the process of the present invention to process high CNT content.

[0074] Parameter change: CNT content increased to 2.0 wt%.

[0075] CNT pretreatment: The amount of dispersant TNADIS was increased to 0.4 g (while maintaining the same proportion).

[0076] Composite powder preparation: The ball milling time was extended to 6 hours to ensure full composite.

[0077] Hot extrusion: The process parameters are the same as in Example 1.

[0078] Performance results: Mechanical properties: Yield strength YS 410 MPa, tensile strength UTS 445 MPa, elongation EL 5.0%.

[0079] Conductivity: 45% IACS.

[0080] The strength is significantly improved, but the plasticity and conductivity decrease with the increase of CNT content, which is a typical characteristic of high-content reinforced composite materials.

[0081] Comparative Example 1 (lacking CNT preprocessing step) Objective: To compare and verify the necessity of CNT chemical-physical synergistic pretreatment.

[0082] Process: Except for the CNT pretreatment step, all other steps are completely replicated from Example 1.

[0083] CNTs were directly dry-mixed with aluminum powder and then ball-milled without any acid or dispersant treatment.

[0084] result: Mechanical properties: Yield strength YS 325 MPa, tensile strength UTS 360 MPa, elongation EL 4.0%.

[0085] Analysis: Due to severe CNT aggregation, not only is the reinforcing effect limited, but it also becomes a stress concentration point, leading to a sharp deterioration in plasticity. This demonstrates that pretreatment is crucial for achieving effective reinforcement.

[0086] Comparative Example 2 (using excessively high hot extrusion temperature) Objective: To verify the key role of "low-temperature extrusion" in inhibiting harmful interfacial reactions (Al4C3 formation).

[0087] Process: Except for the hot extrusion temperature, all other processes are completely replicated from Example 1.

[0088] The hot extrusion temperature is set to 550°C (exceeding the recommended range of 400~500°C of this invention).

[0089] result: Mechanical properties: YS 370 MPa, UTS 395 MPa, EL 3.5%.

[0090] Conductivity: 48% IACS.

[0091] Analysis: High temperature promoted interfacial reaction, generating a brittle Al4C3 phase that severely impaired interfacial bonding strength, leading to a significant decrease in material plasticity, and the strength improvement was not as good as in Example 1. This proves that controlling the temperature below 500℃ is crucial to ensuring interfacial quality.

[0092] Comparative Example 3 (using excessively low hot extrusion temperature / extrusion ratio) Objective: To verify the necessity of "large deformation" for densification and CNT arrangement.

[0093] Process: Change the hot extrusion parameters.

[0094] The hot extrusion temperature was set to 400°C, and the extrusion ratio was reduced to 6:1 (other aspects are the same as in Example 1).

[0095] result: Mechanical properties: YS 340 MPa, UTS 375 MPa, EL 6.0%.

[0096] Conductivity: 45% IACS.

[0097] Analysis: Insufficient temperature and deformation amount resulted in weak bonding between powder particles, incomplete closure of pores, and insufficient shear force to fully disperse and orient CNTs, resulting in overall performance lower than that of Example 1.

[0098] Comparative Example 4 (Comparison with Traditional Melt Stirring Method) Objective: To highlight the advantages of the powder metallurgy route of this invention compared with traditional preparation methods commonly used in the industry.

[0099] Process: The ultrasonic stirring method was used to add 1.0 wt% of untreated CNTs to 6061 aluminum alloy melt at 750℃ and then mechanically stir and ultrasonically treat for 20 minutes.

[0100] The ingots are cast into billets and then subjected to the same hot extrusion (470°C, extrusion ratio 20:1) and T6 heat treatment.

[0101] result: Mechanical properties: YS 305 MPa, UTS 345 MPa, EL 5.5%.

[0102] Conductivity: 43% IACS.

[0103] Interface: Due to the high melt temperature (750℃), Al4C3 will be generated at the interface.

[0104] Analysis: Traditional melt methods have difficulty solving the problems of wetting, dispersion and interfacial reaction of CNTs in molten aluminum. The performance of the composite materials prepared by these methods is even lower than that of the unreinforced matrix alloy (T6 state), which fully demonstrates the superiority of the "low temperature powder metallurgy" approach of this invention.

[0105] Examples 1-3 and Comparative Examples 1-4 are summarized in Table 1.

[0106] Table 1: Comparison of test data between Examples 1-3 and Comparative Examples 1-4

[0107] Examples 4-8 The preparation parameters for Examples 4-8 are shown in Table 2, and the test results are shown in Table 3. For any necessary technical content not mentioned, please refer to the description of the technical solution in the invention content section above and the relevant technical content of Example 1.

[0108] Table 2: Preparation parameters of Examples 4-8

[0109] Table 3: Test Results of Examples 4-8

[0110] Example 4 (Lower Limit Verification Example) aims to verify the feasibility of the lower limit of the process parameter range and the material performance, focusing on the economical process window under low reinforcement content. A CNT content close to the lower limit (0.3 wt%) was selected in the design, and correspondingly, relatively lenient process parameters were adopted: acid treatment temperature was set to 60℃, ultrasonic dispersion power was reduced to 300W, ball milling time was shortened to 2 hours, and the extrusion ratio was set to a low 10:1. This combination of "low content + low energy consumption" aims to explore how to minimize production costs while meeting basic dispersion requirements. Technical results show that the composite material prepared in this example exhibits excellent electrical conductivity (61% IACS) and ductility (elongation 14.5%). Although the strength improvement is relatively mild, it successfully verifies the feasibility of the process of this invention in preparing highly conductive and highly ductile composite materials under low energy consumption conditions, suitable for applications where strength requirements are not high but electrical conductivity and processability requirements are stringent.

[0111] Example 5 (Upper Limit Verification Example) focuses on exploring the performance limits of the technical solution and verifying the process compatibility and dispersion effect under high reinforcement content. Considering the tendency of high-content CNTs (2.8 wt%) to agglomerate, targeted enhanced process measures were adopted: the acid treatment temperature was increased to 80°C, the ultrasonic power was increased to 500W, the ball milling time was extended to 7.5 hours, and a high extrusion ratio of 25:1 and a cold pressing pressure of 600 MPa were applied. This parameter combination follows the engineering logic of "high content requires strong dispersion," aiming to break the CNT agglomeration bottleneck through extreme process inputs. The results show that the material achieved the highest yield strength (425 MPa) and Vickers hardness (168 HV) in this series of examples, proving that the process system of this invention can effectively overcome the dispersion problem caused by high-content reinforcements, preparing high-performance structural materials suitable for applications with extremely high requirements for tensile strength and wear resistance.

[0112] Example 6 (Economical Example) aims to provide an economical process solution that balances performance and cost, filling the data gap between the lower limit and the benchmark example. The design selected a low to medium content of CNTs (0.7 wt%), with process parameters set in the low to medium range, such as a ball milling time of 3.5 hours and an extrusion ratio of 14:1. The design logic is that low to medium content CNTs have moderate dispersion difficulty, achieving uniform distribution without the need for extreme parameters, thereby significantly shortening the production cycle and reducing energy consumption while ensuring product quality. Technical results show that this material exhibits significantly superior strength (yield strength 362 MPa) compared to the matrix alloy, while retaining good plasticity (elongation 11.5%) and conductivity (56% IACS). The balanced and excellent performance across all indicators demonstrates the highly competitive "cost-effectiveness" advantage of this invention in actual large-scale production.

[0113] Example 7 (Comprehensive Balance Example) serves as a typical representative of the technical solution, focusing on demonstrating the balance of comprehensive material properties under moderate parameter levels. A moderate CNT content (1.3 wt%) was selected, and key process parameters—such as ball milling speed (280 rpm), extrusion speed (4 mm / s), and solution temperature (540℃)—were all adjusted to the central region of the recommended range. This design aims to avoid the uncertainties that extreme parameters may introduce and to verify the stability and repeatability of the process window. Results show that the material achieves an optimal trade-off between strength, plasticity, and conductivity under this process, exhibiting minimal fluctuations in mechanical properties and a uniform microstructure. This demonstrates that the process parameter system described in this invention possesses extremely high robustness within the median range and is suitable as a process reference for standardized production.

[0114] Example 8 (Performance-Oriented Example) focuses on high-strength-oriented process optimization, aiming to resolve the contradiction between high strength and low plasticity. A medium-to-high CNT content (2.2 wt%) was selected. While ensuring effective dispersion, deformation and heat treatment parameters were specifically optimized: a high extrusion ratio of 22:1 was used to promote CNT directional alignment and matrix densification, coupled with a longer artificial aging time (10.5 hours) to fully exploit the matrix precipitation strengthening potential. Compared to the extreme strengthening strategy of Example 5, the parameter settings in this example are more refined, avoiding matrix damage caused by over-processing. Technically, the material achieves high strength (yield strength 405 MPa) while maintaining an usable elongation of 6.0% and a conductivity of 47% IACS, demonstrating that through reasonable parameter matching, an optimized match of the strength-plasticity product can be achieved under high-content reinforcement conditions, meeting the needs of complex load-bearing components.

[0115] This invention first employs a synergistic "chemical-physical" pretreatment process for carbon nanotubes (CNTs). First, CNTs undergo acid treatment to purify and functionalize their surface. Then, they are subjected to high-intensity ultrasonic dispersion in a solvent with a specific type and ratio of dispersant. This addresses the agglomeration problem of CNTs at its source, improving their wettability and dispersion stability in subsequent metal powder processes, laying the foundation for uniform composite formation. Based on this, a high-energy ball milling process is used under a protective atmosphere. Through specific ball-to-powder ratios, rotation speeds, time, and intermittent modes, the pre-dispersed CNTs are effectively embedded, pressed, or welded to the surface and near-surface of deformed aluminum-magnesium-silicon alloy powder, forming a "core-shell" structured composite powder. This effectively prevents CNTs from re-agglomerating in subsequent processes. The acid treatment of CNTs to purify and functionalize their surface, followed by high-intensity ultrasonic dispersion in a solvent with a specific type and ratio of dispersant (such as TNADIS), addresses the agglomeration problem of CNTs at its source, improving their wettability and dispersion stability in subsequent metal powder processes. This is the foundation for achieving uniform composite formation.

[0116] This invention achieves micro-mechanical composite formation of CNTs and alloy powders through "high-energy ball milling." High-energy ball milling is performed under a protective atmosphere (such as argon) using a specific ball-to-powder ratio, rotation speed, time, and intermittent mode. Mechanical force effectively embeds, presses, or welds the pre-dispersed CNTs onto the surface and near-surface of the deformed aluminum-magnesium-silicon alloy powder, forming a "core-shell" composite powder and preventing the CNTs from re-agglomerating in subsequent processes.

[0117] For the hot extrusion molding process, this invention establishes a "low temperature-large deformation" process window, strictly controlling the hot extrusion temperature at 400~500℃ (preferably 450~480℃), coupled with a high extrusion ratio (10:1 to 25:1) and a moderate extrusion speed (1~10 mm / s). The low temperature strategy aims to stay below the temperature at which aluminum and carbon react significantly, thereby effectively suppressing the formation of the brittle Al4C3 phase and ensuring interfacial strength and toughness. Large deformation (high extrusion ratio) provides significant shear strain, further breaking down any remaining CNT agglomerates, promoting their directional alignment along the extrusion direction, and achieving complete densification of the composite powder. Speed ​​control is used to balance production efficiency and heat control, preventing localized temperature exceedances due to deformation heat.

[0118] Furthermore, this invention incorporates a continuous "extrusion-quenching" process. Immediately after hot extrusion, the profile undergoes online water mist quenching or forced air cooling, utilizing the residual heat from extrusion to achieve rapid solution treatment. This retains alloying elements such as Mg and Si within the aluminum matrix, preparing it for subsequent aging strengthening and simplifying the process flow. In summary, this invention provides a systematic and stable technical path for the stable preparation of high-performance CNT / Al-Mg-Si composite materials through a complete process chain integration of "CNT pretreatment → mechanical composite powder preparation → cold pressing preforming → low-temperature hot extrusion densification → (online quenching) → short-time solution treatment-aging strengthening," ensuring full controllability from nanoscale dispersion to macroscopic properties.

[0119] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of the claims of the present invention.

Claims

1. A method for preparing an aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite, characterized in that, Includes the following steps: Carbon nanotube pretreatment steps: Acidify the carbon nanotubes, then add a dispersant and ultrasonically disperse them to obtain a carbon nanotube suspension; Mechanical composite step: The carbon nanotube suspension is mixed with aluminum-magnesium-silicon alloy powder and then ball-milled under a protective atmosphere to obtain composite powder; Preform preparation steps: The composite powder is cold-pressed to obtain a preform; Hot extrusion molding step: The preform is heated to 400~500℃ and hot extruded under the conditions of extrusion ratio of 10:1~25:1 and extrusion speed of 1~10 mm / s to obtain the molded composite material. Heat treatment steps: The molded composite material is subjected to solution treatment and artificial aging treatment to obtain the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material.

2. The method for preparing the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite according to claim 1, characterized in that, In the carbon nanotube pretreatment step, the acidification treatment is performed by reflux treatment with concentrated nitric acid at 60~80℃ for 2~4 hours; the dispersant is a nonionic surfactant or anionic dispersant, and the mass ratio of the dispersant to the carbon nanotube is 6:1~10:

1.

3. The method for preparing the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite according to claim 1, characterized in that, In the mechanical compounding step, the ball-to-material ratio of the high-energy ball mill is 5:1 to 15:1, the rotation speed is 200 to 400 rpm, the ball milling time is 2 to 8 hours, and an intermittent ball milling mode is adopted.

4. The method for preparing the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite according to claim 1, characterized in that, In the preform preparation step, the temperature of the hot extrusion molding is 450~480℃.

5. The method for preparing the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite according to claim 1, characterized in that, In the hot extrusion molding step, after the hot extrusion molding is completed, the extruded material is immediately subjected to online water mist quenching or forced air cooling.

6. The method for preparing the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite according to claim 1, characterized in that, In the heat treatment step, the solution treatment temperature is 520~560℃, and the solution is held for 0.5~2 hours before water quenching; the artificial aging temperature is 160~180℃, and the aging time is 6~12 hours.

7. A carbon nanotube-reinforced composite material with an aluminum-magnesium-silicon alloy matrix, characterized in that, The composite material is prepared by any one of claims 1 to 6, and includes an aluminum-magnesium-silicon alloy matrix and carbon nanotubes dispersed in the matrix. The carbon nanotubes are oriented or distributed in a strip shape along the extrusion direction, and there is no large amount of Al4C3 brittle phase at the interface between the carbon nanotubes and the aluminum matrix.

8. The aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material according to claim 7, characterized in that, The mass fraction of the carbon nanotubes in the composite is 0.2 wt% to 3.0 wt%.

9. The aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite material according to claim 7 or 8, characterized in that, The Vickers hardness of the composite material is above 150 HV.

10. The application of the aluminum-magnesium-silicon alloy matrix carbon nanotube reinforced composite as described in any one of claims 7 to 9 in the preparation of power fittings, or in aerospace structural components, or in new energy vehicle battery trays, or in lightweight automotive body frames.